2020
DOI: 10.1177/0042098020963854
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid coordination of city organisations: The rule of people and culture in the shadow of structures

Abstract: Under far-reaching reforms, many cities have delegated core tasks previously delivered by their administrations to independent organisations that they formally own, e.g. municipal companies, or supervise, e.g. municipal trust funds. The coordination of these (as we call them) ‘domestic’ city organisations has proven challenging. Extant literature argues that such coordination is achieved through a mix of various hierarchical, market and network mechanisms. Yet it is unclear how these modes are combined. Addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 64 publications
1
20
0
Order By: Relevance
“…(2) Second, there have been changes in terms of the "where" of PMM (i.e. its locus), as "public organizational landscapes" (Leixnering et al, 2021) continue to undergo significant change, alongside the different organisational forms adopted in the public sector (Meyer and H€ ollerer, 2014;Meyer and Quattrone, 2021). Indeed, the diversity of the "animals in the administrative zoo" (Bach and Jann, 2010) keeps expanding.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Second, there have been changes in terms of the "where" of PMM (i.e. its locus), as "public organizational landscapes" (Leixnering et al, 2021) continue to undergo significant change, alongside the different organisational forms adopted in the public sector (Meyer and H€ ollerer, 2014;Meyer and Quattrone, 2021). Indeed, the diversity of the "animals in the administrative zoo" (Bach and Jann, 2010) keeps expanding.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, other authors have confirmed in their studies that the drive for innovation as a cultural norm determines a strategic change in local government [ 4 ] or engagement in collaboration [ 5 , 6 ]. The importance of organisational culture in the hybrid coordination of city organisations is also considered by Leixnering et al [ 7 ], and they prove that cultural coordination, rooted in the network mode, complements structural coordination, which is associated with hierarchy and market. The cultural mechanisms relieve structural coordination while structural mechanisms provide the shadow in which cultural coordination thrives.…”
Section: Introductionmentioning
confidence: 87%
“…Vienna’s core identity has become defined by a set of values best represented by the motto: a ‘city for everyone’. Accordingly, diverse urban (infra-)structures provide the means to realise these values in various policy fields – not just in housing but also in health and social care, public transport and culture (Leixnering et al, 2020). And it seems that the city has indeed proved rather resilient in this respect.…”
Section: Illustration: Vienna As a ‘Resilient’ City – And The Risk Of...mentioning
confidence: 99%